The effect of travoprost on primary human limbal epithelial cells and the siRNA-based aniridia limbal epithelial cell model, in vitro - Shuailin Li; Tanja Stachon; Shanhe Liu; Zhen Li; Shao-Lun Hsu; Swarnali Kundu; Fabian N. Fries; Berthold Seitz; Maryam Amini; Shweta Suiwal; Nóra Szentmáry (PLoS ONE, 2025)
Purpose Haploinsufficiency of the PAX6 gene is the primary pathogenic mechanism underlying classical congenital aniridia. Notably, at least 50% of patients with this condition develop glaucoma. Prostaglandin analogues, such as travoprost, are widely used to lower intraocular pressure in this patient population. At the same time, limbal epithelial cells (LECs) are believed to play a key role in the development and progression of aniridia-associated keratopathy (AAK). Therefore, the aim of this study was to investigate the effects of travoprost on cell viability, proliferation, migration, and the expression of key genes and proteins in both normal and PAX6-knockdown LECs. Materials and Methods Primary human LECs were isolated from seven corneal donors. To simulate the haploinsufficient state characteristic of congenital aniridia, a PAX6-knockdown model, using siRNA was employed. LECs were treated with 0.039–40 μg/mL travoprost concentration for 20 minutes. Cell viability was assessed using the XTT assay, while cell proliferation was evaluated by the BrdU assay. Based on XTT results, 0.156 and 0.313 μg/mL travoprost were selected for further measurements in both LECs and PAX6-knockdown LECs. A scratch assay was conducted to measure cell migration. The expression levels of PAX6, FOSL2, MAPKs, inflammatory markers, caspase-3, and MMP9 were analyzed at both the gene and protein levels using qRT-PCR, Western blot, and ELISA. Results Travoprost significantly reduced LEC viability at 0.156 μg/mL (p = 0.028), while only higher concentrations (20 and 40 μg/mL) inhibited significantly LEC proliferation (p ≤ 0.004). PAX6-knockdown LECs exhibited reduced migration compared to control cells (p ≤ 0.046); however, treatment with 0.313 μg/mL travoprost significantly enhanced their migration (p = 0.047), accompanied by upregulation of JNK1/2 protein (p = 0.039) and MMP9 mRNA and protein levels (p = 0.021, p = 0.027). PAX6 knockdown led to suppression of inflammation-related genes (p ≤ 0.031) and travoprost did not exacerbate inflammatory responses (p ≥ 0.155). Additionally, 0.313 μg/mL travoprost significantly increased caspase-3 protein levels in PAX6-knockdown LECs (p = 0.044). Conclusions Travoprost, at specific concentrations, can reduce the viability and proliferation of limbal epithelial cells. At 0.313 μg/mL, it significantly upregulates JNK1/2 and MMP9 expression, thereby enhancing the migratory capacity of PAX6-knockdown LECs. These findings may offer valuable insights for the selection of antiglaucomatous medications in patients with congenital aniridia.